2010
DOI: 10.1177/1721727x1000800201
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Bradykinin System by Angiotensin-Converting Enzyme Inhibitors

Abstract: The Bradykinin (BK) system has a very significant role in the regulation of blood pressure (BP). Hence, reduced activity of BK receptors mediated via decreased circulating endogenous kinin might explain the cause of high BP. This system also governs the activation of the angiotensin system at various axes in control of the physiological BP. The BK receptor antagonists can block the hypotensive action of angiotensin-converting enzyme inhibitors (ACEls) in hypertensive and normotensive animals. The hypotensive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In this patient population, those within the highest quartile of IL-18 had a 3.3-fold increase in hazard risk compared to those in the first quartile (18). In addition, data from the Prospective Epidemiological Study of Myocardial Infarction (PRIME) demonstrate an independent association between baseline plasma IL-18 concentration in healthy middle-aged men and future coronary events (19)(20)(21). This association remains after adjustment for classic cardiovascular risk factors.…”
Section: Interleukin-/8mentioning
confidence: 99%
“…In this patient population, those within the highest quartile of IL-18 had a 3.3-fold increase in hazard risk compared to those in the first quartile (18). In addition, data from the Prospective Epidemiological Study of Myocardial Infarction (PRIME) demonstrate an independent association between baseline plasma IL-18 concentration in healthy middle-aged men and future coronary events (19)(20)(21). This association remains after adjustment for classic cardiovascular risk factors.…”
Section: Interleukin-/8mentioning
confidence: 99%
“…It is the generally accepted view that the BK-induced BP lowering effect is mediated by the B 2 receptor, but B 1 receptor might also be involved under special situations [41]. It has been demonstrated that a B 2 receptor antagonist (B5630) can generally abolish the hypotensive effects of BK as well as captopril, an ACEI [42]. This led to the proposal that the hypotensive action of ACEIs might be due to the activation of B 2 receptor.…”
Section: Hypertension and The Kinin Systemmentioning
confidence: 99%
“…Interestingly, the selective pseudopeptide B 2 receptor antagonist HOE-140 (Icatibant) has been approved in the Americas and Europe, for managing acute episodes of hereditary angioedema, under the commercial name Firazyr [ 15 ]. Additionally, the therapeutic benefits of ACE inhibitors, such as captopril, also rely on the modulation of kinins and their biological effects [ 16 ]. Over the last four decades, the role of either kinin receptor and other components of the kinin system has been described in a series of infectious conditions, such as sepsis, schistosomiasis, leishmaniosis, Chagas Disease, candidiasis, tuberculosis, malaria, and it has been recently correlated with Covid-19 infection [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%